Geographische Interpretation einer Grünland-Vegetationskarte der südbadischen Rheinebene - Krause, Werner (ERDKUNDE, 1966)
Vegetation maps of intermediate scales which show more extensive areas in considerable differentiation draw the attention towards the coincidence of the pattern of plant cover and geographical structure. As it is possible to observe the vegetation in its entire extent, its mapping serves as an easily applicable method to elucidate otherwise more or less obscured relationship. The paper shows on the example of the grassland-vegetation map (1 : 100 000) of an apparently monotonous area approximately 150 km. by 8-12 km. how the distribution pattern of the plant associations and their ecological value-indices facilitate an insight into the hydro-ecology of locations. In detail the following classification emerges: 1) Permeable ground, water provision by ground water. 2) Ground capable to store water, water provision by superficial drainage and rain. 3) Ground capable of storing water. Water provision by rain. 4) Ground permeable without contact with ground water. Very dry. The paper further demonstrates the consequences of a former land use system on the present vegetation as well as the detailled ecological structure of a gravel fan.